Perirenal Lucency (Kidney Sweat) A New Sign of Renal Failure - Huda, MD; Ahmed, AU; Mohiuddin, AS (TAJ: Journal of Teachers Association, 2009)
This prospective study was designed to find out the sensitivity, specificity and predictive values of ("kidney sweat") sign in the sonographic diagnosis of renal failure and carried out in the department of radiology and imaging BIRDEM, Dhaka and BSMMU, Dhaka. For this purpose 146 patients referred for renal sonogram were examined. Out of which 50 patients did not have clinical or laboratory evidence of renal failure and did not show "Kidney sweat" sign (Perirenal hypoechoic rim) in their sonogram. In this work out of 96 renal failure patients eleven (11.46 percent) showed "Kidney sweat" sign in their sonogram. This might be an additional sonographic finding of chronic renal failure patients. doi: 10.3329/taj.v18i2.3195 TAJ 2005; 18(2): 134-136